2015
DOI: 10.5826/dpc.0502a20
|View full text |Cite
|
Sign up to set email alerts
|

Complete regression of a melanocytic nevus after epilation with diode laser therapy

Abstract: The use of lasers and intense pulsed light (IPL) technology has become an established practice in dermatology and aesthetic medicine. The use of laser therapy and IPL in the treatment of pigmented melanocytic lesions is a controversial issue. We report clinical, dermoscopic and histological changes of a completely regressed pigmented melanocytic nevus after hair removal treatment with the LightSheer™ Diode Laser (Lumenis Ltd, Yokneam, Israel).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…They also showed that grayish area or milky red veil reflects collagen degeneration on the upper dermis that is the result of inflammatory reaction caused by acute thermal injury. [7][8][9]11,12 Micro-crust usually appeared a few days after photo-irradiation of pigmented lesions. It is explained by destruction of epidermal melanin containing cells and promotion of a rapid differentiation of keratinocytes that leads to an upward transfer of melanocytes along with necrotic keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They also showed that grayish area or milky red veil reflects collagen degeneration on the upper dermis that is the result of inflammatory reaction caused by acute thermal injury. [7][8][9]11,12 Micro-crust usually appeared a few days after photo-irradiation of pigmented lesions. It is explained by destruction of epidermal melanin containing cells and promotion of a rapid differentiation of keratinocytes that leads to an upward transfer of melanocytes along with necrotic keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic or electron microscopy studies showed this homogeneous disorganized pigmentation is compatible with micro‐crust composed of keratinocyte debris and numerous melanosomes. They also showed that grayish area or milky red veil reflects collagen degeneration on the upper dermis that is the result of inflammatory reaction caused by acute thermal injury 7‐9,11,12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases of clinical and corresponding dermoscopic as well as histologic changes were noted to present as early as 15 days after treatment and some had persistent or progressive changes at the last time of follow up, as far as 3 years postexposure. 10,15 Commonly reported changes in studies include complete or partial regression, decreased size, laser induced asymmetry, bleaching, darkening, and altered pattern on dermoscopy, namely changes to the reticular or dot globule pattern. 16,17 Regression, asymmetry, gray areas, and loss of pigment network were alterations reported in multiple cases.…”
Section: Resultsmentioning
confidence: 99%